'Twas Tír na nÓg itself': The Muckross Music Collection: fieldwork in North Kerry 1980–1990. (2nd July 2016) - Mitchell-Ingoldsby, Mary
Abstract : This paper gives an account of the establishment of the Muckross Music Collection project in 1980 and of the author's participation as a collector for the initiative from 1983 to 1990. The paper discusses methodologies and approaches adopted by the organizers for the collecting and the cataloguing of the materials. The account of the processes and encounters involved in fieldwork provides insights into motivations, expectations and results. The large number of musicians in a small area around Listowel in North Kerry revealed a rich ground for the collection of music. Likewise, repertoire varied according to individual and district. Narratives accompanying the tunes abounded. Players understood the importance and prestige of the project and that their music, largely unrecorded previously, would be preserved for the future. Sometimes the collector missed an opportunity due to a musician's death. The paper indicates the value of this collection for future research projects on the history and ethnography of Irish traditional music in the twentieth century.